2021
DOI: 10.1001/jamasurg.2021.3651
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning to Automate Technical Skills Assessment in Robotic Surgery

Abstract: Surgeon performance affects patient outcomes. 1 To improve patient outcomes, we must identify poor surgical performance. However, surgeons may not always associate a specific surgical act with its consequential outcome unless the error is egregious and the outcome is immediate. Today, there is little formal structure for surgeons to receive specific technical skills feedback after formal training. Current hurdles for surgeons to obtain and maintain hospital privileges to perform an operative procedure include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Throughout surgical data science, researchers are interested in exploring the associations among surgeon characteristics, tool movement, task outcome, and, eventually, patient outcome, complication occurrence, and technical competency. 44 Surgical video is the primary data source for this information for most operations aside from a few robotic-assisted procedures. 45 , 46 , 47 Despite its importance, no publicly available data sets exist of surgical video labeled with clinically meaningful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout surgical data science, researchers are interested in exploring the associations among surgeon characteristics, tool movement, task outcome, and, eventually, patient outcome, complication occurrence, and technical competency. 44 Surgical video is the primary data source for this information for most operations aside from a few robotic-assisted procedures. 45 , 46 , 47 Despite its importance, no publicly available data sets exist of surgical video labeled with clinically meaningful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 On this aspect, we have used a deeplearning algorithm to automate suturing technical skill assessment in the virtual-reality environment and achieved promising preliminary performance. 26 Though the present study identified feasible and effective feedback based on clinically relevant outcomes to improve surgeon performance, there are some limitations. First, this was a pilot study with a limited sample size.…”
Section: Discussionmentioning
confidence: 88%
“…24,25 On this aspect, we have used a deep-learning algorithm to automate suturing technical skill assessment in the virtual-reality environment and achieved promising preliminary performance. 26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations